Decomposition of 2Km,n into short cycles - Chou, Chao-Chih; Fu, Chin-Mei; Huang, Wen-Chung (Utilitas Mathematica, 2000)
Let 2Km,n be the 2-fold complete bipartite graph and Cr be an elementary cycle of length r. In this paper, it is shown that 2Km,n can be decomposed into p copies of C4, q copies of C6, and r copies of C8, for each triple p, q, r of nonnegative integers such that 4p + 6q + 8r = 2mn for each m, n ≥ 4.